Fighting State Negligence: Class Action Lawsuits as an Instrument of Justice for Flood Victims (An Analysis of the Banjarmasin State Administrative Court Decision and its Relevance for West Java Flash Floods 2025) - Attidhira, Safira Widya; Suparno (Jurnal Greenation Sosial dan Politik, 2025)
Class action lawsuits have become an important instrument in fighting for justice for victims of natural disasters in Indonesia, as seen in the 2021 South Kalimantan flash flood case. This study analyzes the effectiveness of class action lawsuits as a corrective justice mechanism under Law No. 24 of 2007 on Disaster Management by examining the Banjarmasin State Administrative Court Decision No. 6/PEN-HS/2021/1/PTUN.BJM and its relevance to the West Java 2025 flash flood. Through a juridical-normative approach with document analysis of court decisions, the research shows that although the lawsuit required significant resource mobilization and was unsuccessful in obtaining material compensation that should have been the right of victims according to Article 26 letter (d) of Law No. 24 of 2007, it proved effective in forcing disaster management policy reform. The South Kalimantan case led to the procurement of an early warning system worth IDR771.5 million and supporting infrastructure worth IDR2.2 billion. Comparative analysis identified similar patterns of institutional negligence in both disasters: unpreparedness of early warning systems, slow emergency response, and neglect of the impact of environmental damage due to land conversion. This research confirms that despite evidentiary challenges and bureaucratic resistance, class action lawsuits remain a vital instrument in promoting government accountability and structural reform in disaster management as mandated by Law No. 24/2007.